(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To compare morphometric changes in the chorioretinal complex after anti-vascular endothelial growth factor (anti-VEGF) treatment in patients with pathologic myopia (PM)-related choroidal neovascularization (CNV) versus those with age-related macular degeneration (AMD)-related CNV. Materials and Methods: This was a prospective comparative uncontrolled cohort study involving 156 patients (169 eyes) with subfoveal CNV. Of these, 82 (85 eyes) had pathologic PM-related CNV, and 74 (85 eyes) had AMD-related CNV. Patients with AMD underwent a treatment regimen of three mandatory monthly 0.5-mg (0.05-mL) intravitreal ranibizumab injections followed by pro re nata (PRN) dosing according to re-treatment criteria. Patients with PM underwent a treatment regimen of two mandatory monthly 0.5-mg (0.05-mL) intravitreal ranibizumab injections or 2-mg (0.05-mL) intravitreal aflibercept injections followed by PRN dosing according to re-treatment criteria. Primary outcomes were central retinal thickness (CRT) and CNV thickness at month 12. Secondary outcomes included best-corrected visual acuity (BCVA) and number of injections at month 12. Results: At month 12, (1) mean OCT-based CRT in AMD and PM groups decreased from 349 μm to 258 μm (P = 0.00), and from 306 μm to 228 μm (P = 0.00), respectively, and (2) mean CNV thickness in AMD and PM groups decreased from 183 μm to 108 μm (P = 0.00), and from 229 μm to 173 μm (P = 0.00), respectively. In addition, mean (SD) BCVA in the AMD group improved from 0.25 (0.23) at baseline to 0.33 (0.29), whereas that in the PM group improved from 0.17 (0.11) to 0.35 (0.19). The mean number of anti-VEGF injections was 5.4 (2.1) and 2.2 (0.6) for the AMD and PM groups, respectively, with the between-group difference being statistically significant (P = 0.00). Conclusions: Decrease in central retinal thickness and improvements in visual acuity after anti-VEGF treatment for AMD-related subfoveal CNV were similar to those after anti-VEGF treatment for PM-related subfoveal CNV. At month 12, percent decreases in CNV thickness compared to baseline were 26% and 41% for anti-VEGF treated patients with AMD-related and PM-related subfoveal CNV, respectively. Patients with AMD-related CNV required, on average, 3 more anti-VEGF injections than those with PM-related CNV.